Analysis of Cohesive Reference in President Buhari’s 2020 End-SARS Speech - ABUBAKAR , Bashir; MODU , Muhammad Mallam; USMAN , Musa Mohammed (International Journal of Arts, Languages, Linguistics and Literary Studies, 2023)
For a text to pass across intended meanings and to be understood, it must encode the meanings properly through achieving cohesion. In essence, this paper aims to identify, describe and examine the necessity of the cohesive reference used in president Buhahi end-SARS speech. This speech is analysed based on the Halliday and Hasan (1976), Eggins (2004), and Imtiaz & Ghufran (2020) cohesion theory. This is because individuals communicate their ideas, feelings and thoughts through language in which speech is crucial. Library research approach is used as a means of collecting required data. In the process, all the materials used were gotten from the library and the internet. The speech shows clear evidence of cohesion and demonstrates the use of cohesive reference devices. The results reveal that there is sufficient indication of using categories of reference devices which include the use of homophoric, exophoric and endophoric reference. The usage indicates that the speech writer addresses the issue in both immediate context and general context. Among them, the exophoric reference, as a cohesion marker, is mostly used in the speech. This reflects what is considered as consistent degree of context-dependency for a text which is apparently about events in the real world. Thus, this paper forms an input to the study of the ways in which various forms of reference between sentences within texts contribute to the insight of cohesion which such texts produce to audiences.